SOX10-MITF pathway activity in melanoma cells - Tudrej, Karol B.; Czepielewska, Edyta; Kozłowska-Wojciechowska, Małgorzata (Archives of Medical Science, 2017)
Melanoma is one of the most dangerous and lethal skin cancers, with a considerable metastatic potential and drug resistance. It involves a malignant transformation of melanocytes. The exact course of events in which melanocytes become melanoma cells remains unclear. Nevertheless, this process is said to be dependent on the occurrence of cells with the phenotype of progenitor cells – cells characterized by expression of proteins such as nestin, CD-133 or CD-271. The development of these cells and their survival were found to be potentially dependent on the neural crest stem cell transcription factor SOX10. This is just one of the possible roles of SOX10, which contributes to melanomagenesis by regulating the SOX10-MITF pathway, but also to melanoma cell survival, proliferation and metastasis formation. The aim of this review is to describe the broad influence of the SOX10-MITF pathway on melanoma cells.